Pertumbuhan Rumput Laut Kappaphycus alvarezii (Doty, 1985) dengan Metode Lepas Dasar - Prayudha, Muhammad Rifky; Pramesti, Rini; Susanto, AB (Universitas Bengkulu, 2024)
Environmental factors have affected seaweed cultivation. Productivity can be increased by using the right method. Seaweed production is related to brightness and photosynthetic processes which are affected by planting depth. This study aims to examine the effect of differences in depth on the growth rate of K. alvarezii with the off-bottom cultivation method in the waters of Lontar Village, Serang Regency, Banten Province. Randomized Block Design was used as the experimental design in this study. Cultivation depth of 30 cm, 50 cm and 70 cm were used as different treatments, each with three groups and 5 replications. The growth of sample weight was observed every week for six weeks as the main parameter. Water quality (temperature, salinity, brightness, pH, current velocity, nitrate, phosphate and dissolved oxygen) was observed as another parameter. The results showed that weight growth is influenced by the depth of cultivation. The 30 cm depth has the highest growth rate with an absolute growth of 890 grams and a specific growth rate of 2.85% per day. Keywords : Kappaphycus alvarezii, depth, growth rate